2017
DOI: 10.4236/health.2017.91003
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Family History of Cancer among Gastric Cancer Patients at Brazilian National Cancer Institute

Abstract: Background: Gastric cancer is the third most incident malignancy and the fifth leading cause of death in the world. In Brazil, it is the fourth most common tumour in men and the fifth in women. Familial aggregation of this tumour is being studied and discussed by experts. Aim: Determine the frequency of family history of cancer in patients with gastric cancer, suggesting familial aggregation or increased risk for hereditary cancer syndromes. Methods: This is a retrospective cross-sectional study carried out fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
(17 reference statements)
0
3
0
1
Order By: Relevance
“…Gastric cancer (GC), which affects > 950,000 patients annually, is the fifth most prevalent cancer and the third most common cause of cancer-related death worldwide [1][2][3]. Epidemiological studies have shown that the overall incidence of GC is decreasing, likely because of changes in lifestyle, such as lower salted and preserved food intake and reduced Helicobacter pylori infection.…”
Section: Introductionmentioning
confidence: 99%
“…Gastric cancer (GC), which affects > 950,000 patients annually, is the fifth most prevalent cancer and the third most common cause of cancer-related death worldwide [1][2][3]. Epidemiological studies have shown that the overall incidence of GC is decreasing, likely because of changes in lifestyle, such as lower salted and preserved food intake and reduced Helicobacter pylori infection.…”
Section: Introductionmentioning
confidence: 99%
“…Affecting more than 950,000 patients annually, gastric cancer (GC) is the fth most prevalent cancer and the world's third most common cause of cancer-related death [1][2][3] . Epidemiological studies have shown that the overall incidence of GC is decreasing, likely as lifestyle changes are occurring, such as lower salted and preserved food intake, and reduced Helicobacter pylori 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…La mutación de la línea germinal en el gen e-cadherina es responsable del síndrome de cáncer gástrico dominante autosómico familiar que conduce al desarrollo de cáncer gástrico a una edad temprana. Los criterios para sospechar el síndrome incluyen un individuo diagnosticado con cáncer gástrico antes de los 50 años, o dos o más generaciones sucesivas de familias afectadas (1,14,15) .…”
Section: Discussionunclassified